2020
DOI: 10.1371/journal.pone.0239509
|View full text |Cite
|
Sign up to set email alerts
|

Optimised neural network model for river-nitrogen prediction utilizing a new training approach

Abstract: In the past few decades, there has been a rapid growth in the concentration of nitrogenous compounds such as nitrate-nitrogen and ammonia-nitrogen in rivers, primarily due to increasing agricultural and industrial activities. These nitrogenous compounds are mainly responsible for eutrophication when present in river water, and for 'blue baby syndrome' when present in drinking water. High concentrations of these compounds in rivers may eventually lead to the closure of treatment plants. This study presents a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…Meteorological conditions such as monsoon and precipitation rate are persistent factors for environmental change yet little to no studies have incorporated such parameters into the modelling of ecosystem quality for pollution prediction. A relation of meteorological data was identified between the prediction of heavy metals in water bodies or nitrogen and turbidity concentration [116,145,150]. Moreover, meteorological and climatological variables were found to have a profound impact on soil distribution, where air temperature could complement the prediction of soil temperature [193].…”
Section: ) Conceptual Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…Meteorological conditions such as monsoon and precipitation rate are persistent factors for environmental change yet little to no studies have incorporated such parameters into the modelling of ecosystem quality for pollution prediction. A relation of meteorological data was identified between the prediction of heavy metals in water bodies or nitrogen and turbidity concentration [116,145,150]. Moreover, meteorological and climatological variables were found to have a profound impact on soil distribution, where air temperature could complement the prediction of soil temperature [193].…”
Section: ) Conceptual Modelmentioning
confidence: 95%
“…Hydrological and climatological data were used by Kumar, et al [145] and Song and Zhang [150] to predict nitrogen and turbidity values respectively. The model built in both studies were effective and reliable, suggesting the importance of environmental factors to predict water quality.…”
Section: Figure 3 Relation Of Input Attributes Modelling Techniques and Performance Metrics Of Water Quality Prediction Reviewed In This mentioning
confidence: 99%
“…Within this module, bottom dissipation, whitecapping, and depth induced breaking are fully accounted for in a dissipation term (Booij, Ris, & Holthuijsen, 1999). ANN, sometime referred to as black-box (Akrami, El-Shafie, & Jaafar, 2013;Pavitra Kumar et al, 2021), mimics the human brain structure (El-Shafie, Noureldin, Taha, Hussain, & Mukhlisin, 2012;P. Kumar et al, 2020) to provide variables predictions through establishment of relationships between them and other pre-define inputs (Akrami et al, 2013).…”
Section: Fig 1 Morecambe Bay Model Domain and Bathymetry With Observa...mentioning
confidence: 99%
“…Weights and biases are not updated in the validation process. Testing dataset is used for testing the final predictive strength of the model (P Kumar et al, 2020)…”
mentioning
confidence: 99%
“…One of these limitations is the complexity and complicated architecture and the difficulties in initializing the input parameters for these hybrid models 37 . Kumar et al 38 found that the artificial neural network's prediction performance can be enhanced by improving the training approach without hybridizing it with optimization algorithms. In addition to that, a recent study highlighted the importance of the input combinations of ML algorithms' output accuracy, where the optimal input combinations can lead to a high level of accuracy without the need to augment ML with optimizers 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%